ANALISIS HUKUM TERHADAP KEADILAN DALAM PENYELESAIAN SENGKETA PERTANAHAN DI SULAWESI TENGAH PADA TAHUN 2024 - Askaruddin, Muh (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2025)
Land disputes in Central Sulawesi continue to be a crucial issue that threatens legal justice and social stability. This research aims to analyze how the legal system, particularly through mediation mechanisms by the National Land Agency (BPN), has been applied to resolve land conflicts in the region. Using a juridical-sociological approach and qualitative methods, this research examines the effectiveness of the mediation process and the extent to which the principles of substantive justice are reflected in practice. The results show that although mediation is the preferred method, there are still various structural barriers, including unequal access to legal information, limited human resources in relevant agencies, and lack of participation of indigenous peoples. This research recommends the need for institutional reform and increased legal literacy of the community as steps towards a more equitable and sustainable resolution of land disputes.